The Concept of Profit Sharing in The Industrial Field in Islamic Economic - Mujahidin Mujahidin (IAIN Palopo, 2021)
Profit sharing schemes are very limited compared to fixed income schemes, murabaha and ijarah contracts are far more widely used by Islamic financial institutions than profit sharing schemes. the purpose of this research is to know the concept of profit sharing in the industrial field in islamic economy. This research method uses systematic literature review Literature review aims to make an analysis and synthesis of existing knowledge related to the topic to be researched to find empty space for research to be carried out. The results of this study found that Sharia Banking stipulates that mudharabah is what is meant by